Tap, Move, Shake - Moore, Todd (O'Reilly Media, Inc., 2011)
Got a great game idea? This complete do-it-yourself guide shows you how to make your game idea a reality for the iPhone and iPad. By developing a real game hands-on through the course of this book, you'll get a thorough introduction to Xcode and Objective-C, while learning how to implement game logic, sophisticated graphics, game physics, sounds, and computer AI. Author Todd Moore taught himself how to create an iPhone game in a week, with no previous knowledge of Apple's development tools. Now he develops smartphone games and apps full time. With this book, any coder can turn game ideas into real products, ready for the App Store. Get started by writing a simple game in only 20 lines of code Build a complete air hockey game from scratch Learn best practices for tracking multiple screen touches Use animation loops and create collision functions Get the tools you need to build your own stunning game graphics Apply game physics to give your game a sense of realism Record and edit lifelike sound effects, and create your own background music Design a computer player with different levels of difficulty Featuring an introduction by Steve Wozniak Todd Moore founded TMSOFT to create unique smart phone applications and games. His most popular game title, Card Counter, was featured by Engadget, the Los Angeles Times , and CNET TV. Todd's most popular application, White Noise, was featured by iTunes, Health Magazine , The Washington Post , PC Magazine , and Late Night with Jimmy Fallon.